(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
Ornamental plants are of high economic interest, among the most commercially ornamental ones are orchids of the genus Phalaenopsis. In vitro cultivation, a biotechnological toll, aims to propagate a high number of seedlings with phytosanitary quality and is widely used for ornamental cultivation, bioinformatcs assists in the search for similar genomes of organisms that keep theis data stored. The objective of this work was to determine the appropriate culture médium for germination and development of hybrid Phalaenopsis, and to analyze by bioinformatics similar componentes that may replace the studied componente. Four treatments were tested: Knudson culture médium, Murashige and Skoog médium, Knudson growth regulation médium combining a cytokine with na auxin (BAP/ANA), and the last treatment Knudson médium supplemented with carrot juice by 10% (v/v). The results show that carrot juice is beneficial for the germination and development of orchids of the genus Phalaenopsis, and the treatment that obtained the best results in the analyzes performed through the bioinformatics analysis using CLUSTAL and BLAST. A substitute for carrots in the making of culture media is Orange, due to the similarity of the gene responsible for β-caroteno in both.